The Hybrid PV–Micro-Hydro Power System with Automatic ECS in Semi Off-Grid Scheme - Hidayat, Saepul Hidayat; Sucita, Tasma; Washimudin Surya Saputra (Faculty of Engineering, Universitas Brawijaya, 2026)
This study investigated the design and implementation of a hybrid photovoltaic (PV)–micro-hydro power system equipped with an automatic Energy Control System (ECS) in a semi off-grid configuration. The research addressed the challenge of providing reliable and continuous electricity in rural and remote areas where access to the national grid was limited or unreliable. The proposed system combined two 550 Wp monocrystalline PV panels and thirty-two pipeline micro-hydro generators with a total output of approximately +550 VA, supported by a 25.6 V 200 Ah LiFePO? battery bank and a 2000 W pure sine wave inverter. The ECS was designed to manage seamless switching between power sources, regulate charging processes, and ensure uninterrupted electricity supply to household loads. The results showed that the hybrid system generated an average of 12.48 kWh per day, meeting the typical household demand in Indonesia. Economic analysis indicated that monthly electricity costs were reduced by more than 85% compared to full reliance on the national grid. Furthermore, the system maintained 24-hour electricity availability by utilizing solar energy during the day, micro-hydro power during water usage peaks, and battery storage during off-peak periods. Overall, the hybrid PV–micro-hydro system with ECS proved to be a cost-effective, reliable, and sustainable solution for household-scale energy supply in semi off-grid areas.